(untitled) (FULafia Journal of Science and Technology, 2026)
Shiitake mushroom is recognized for its nutritional and bioactive properties, with potential benefits in poultry nutrition. Fermented feed ingredients, such as fermented solid waste product of sugar industry meal, have also gained attention in improving nutrient utilization and growth performance in poultry. This study evaluated the effects of dietary supplementation with Shiitake mushroom on the growth performance of broiler chickens fed diets of fermented SWAPSI meal during an eight-week feeding period divided into starter and finisher phases. A total of 250 broiler chicks were assigned to 5 dietary treatments receiving diets containing varying inclusion levels of Shiitake mushroom combined with fermented SWAPSI meal with 50 birds per treatment and 10 birds per replicate. Initial body weights were similar across treatments. Significant improvements (P<0.05) in final body weight and average weight gain were observed in birds supplemented with 5 % (1391.20 g) and 20 % (1319.80 g) shiitake mushroom compared to the control (788.40 g) and 30 % (715.80 g) groups of finisher phase. In conclusion, 20 % supplementation of Shiitake mushrooms with fermented SWAPSI meal-based diets enhanced growth performance and feed efficiency in broiler chickens.